Nurses' Performance Regarding Arthroplasty and Patients' Safety Measures - Fatma Habib Mohamed Mahmoud , Fathia Attia Mohamed , Naglaa Abd ElKareem Moghazy , and Fatma Mohamed Abdelhamid (Cuestiones de Fisioterapia, 2024)
Background: Arthroplasty (knee and hip) are effective treatments for late-stage osteoarthritis (OA) and have the potential to substantially increase patient quality of life after the surgery. The aim of this study was to evaluate the nurses' performance regarding arthroplasty and patients' safety measures.